First Nations leadership development within a Saskatchewan context - Ottmann, Jacqueline (2005)
The Saskatchewan First Nations leadership development study is essentially a continuation of my previous research on First Nations leadership and spirituality (2002). The purpose of this study was to explore First Nations leadership and leadership development in Saskatchewan within the Federation of Saskatchewan Indian Nations organizational context. To accomplish this, the study involved an extensive literature review on Indigenous and Western leadership and leadership development theories. Further, an examination of four established and prominent North American Indigenous leadership development programs was conducted to gain further understanding of Indigenous leadership. In addition, 10 First Nations leaders from the Federation of Saskatchewan Indian Nations participated in in-depth interviews. Qualitative inquiry was chosen for this study because qualitative research methods were congruent with First Nations methods of sharing and preserving information. In-depth interviews with semi-structured questions were conducted to obtain information on Saskatchewan First Nations leadership and leadership development. All but one participant agreed to the use of an audio taped interview. Once the interviews were complete, Atlas-ti, a computer software program, was used to assist in the coding, categorizing, and thematic emergence process. The four Aboriginal leadership development programs that were examined were University of Arizona’s Native Nations Institute for Leadership, Management, and Policy, Pennsylvania State’s American Indian Leadership Program, Banff Centre’s Aboriginal Leadership and Management Program, and the Aboriginal Leadership Institute Incorporated, located in Winnipeg. These programs strived to remain current and were involved in research initiatives. Moreover, they all attempted to incorporate First Nations culture, history, and issues alongside Western leadership skills, training, and education. They evolved, adapted, and were sensitive to change and innovation in leadership development. First ...